2016
DOI: 10.3109/02713683.2016.1170854
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Corneal Thickness Measurements Using Pentacam Scheimpflug Camera, Noncontact Specular Microscopy, and Ultrasonographic Pachymetry in Diabetic Patients

Abstract: SM-UP pair showed a higher agreement in diabetic patients. According to subgroup analyses, Hb A1c level, rather than the duration of diabetes, may determine the agreement of these pachymetry devices. But the difference in CT measurements between devices can still influence clinical diagnosis and treatment. Therefore, these methods are not completely interchangeable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 25 publications
1
12
0
7
Order By: Relevance
“…Unlike the wide agreement in lens changes of DM patients, it is still controversial whether corneal thickness is affected in DM patients. The discrepancies among different reports could be different devices that are used in CCT measurement, and the HbA1c level may determine the agreement of each pachymetry devices according to Altay et al [14]. The outcomes in our study were similar to Wiemer et al and Uzel et al, the mean CCT, K1, and K2 showed no significant difference between 2 groups.…”
Section: Discussionsupporting
confidence: 68%
“…Unlike the wide agreement in lens changes of DM patients, it is still controversial whether corneal thickness is affected in DM patients. The discrepancies among different reports could be different devices that are used in CCT measurement, and the HbA1c level may determine the agreement of each pachymetry devices according to Altay et al [14]. The outcomes in our study were similar to Wiemer et al and Uzel et al, the mean CCT, K1, and K2 showed no significant difference between 2 groups.…”
Section: Discussionsupporting
confidence: 68%
“…Wirbelauer et al [34] found (541 AE 43) μm for the mean central corneal thickness of 108 subjects (age range: 25-87 years). Altay et al [35] reported mean values on 137 subjects (age range: 18-64 years) equal to (522 AE 34), (543 AE 34), and (538 AE 35) μm, measured by Scheimpflug camera, specular microscopy, and ultrasound pachymetry, respectively. Compared to other techniques, the measurement of corneal thickness with the slit-lamp biomicroscope adds no extra costs for the clinicians, who routinely use this instrument.…”
Section: In Vivo Resultsmentioning
confidence: 99%
“…The aim of this study was to determine the impact of DM on CCT and its correlation with diabetes duration and glycated haemoglobin (HbA1c) levels. Several studies show a significant increase in CCT values in DM patients, 3,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30 although the mechanism responsible for these changes in corneal structure and function remains to be fully understood. Some studies have found a correlation between DM duration and the increase of CCT values, 17,20,25 and others have observed an increase in CCT values when glycated haemoglobin (HbA1c) levels are elevated.…”
Section: Aimmentioning
confidence: 99%